New financial instruments and innovations in the Jamaican economy : implications for monetary policy and financial regulation - Robertson, Hillary ([Caribbean Centre for Money & Finance] [St. Augustine]TT, 1995)
Highlights innovations in the Jamaican financial system during the post-reform period of the late 1980s and the early 1990s.